Efektivitas Penggunaan Tepung Pisang Candi (Musa paradisiacal Fa Corniculata) Dalam Pengaplikasian Cookies Lidah Kucing Ditinjau Dari Sifat Kimia Dan Sifat Fisik - Hesty Wulandari; Budi Wibowotomo; Wiwik Wahyuni (Journal of Food Technology and Agroindustry dipublikasikan oleh Universitas Wiraraja, 2023)
Cookies are a pastry product that is popular and favored by all circles of society. The characteristics of cookies are crunchy texture, brittle, dry, brownish yellow, has a distinctive aroma, savory and also sweet. Basically, cat's tongue cookies are made from flour, the selection of the best factors starting from the color, texture, aroma and taste of cat's tongue cookies made from temple banana flour is able to replace flour as a basic ingredient with the aim of adding diversification of pastry products based on the availability of food ingredients. This study aims to determine the difference between chemical properties (carbohydrate, protein, fiber, moisture content, ash content) and physical properties (breakability and color). This research is an experimental study using a completely randomized design (CRD) in the manufacture of cookies made from 100% temple banana flour and 100% wheat flour. Data were analyzed using Independent Sample T-test.The results of the analysis of chemical properties (carbohydrates, protein, fiber, moisture content, ash content) showed that there was a significant difference while for the water content there was no significant difference. The chemical properties of the carbohydrate content of cookies made from Candi banana flour are 73.31%, protein content is 11.58%, fiber content is 0.65%, water content is 3.84%, ash content is 1.84%. The results of the analysis of physical properties (broken strength, color brightness level (L), reddish level color a(+) showed a significant difference while at yellow level color b(+) there was no significant difference, physical test of cat's tongue cookies made from temple banana flour for fracture strength 0.0060kgf/cm2, color brightness level (L) 67.12%, reddish level color a(+) 3.80%, and yellowish level color b(+) 31.10%.